Natural history and clinical features of ALS in Malaysia. Issue 1 (2nd January 2021) - Abdul Aziz, Nur Adilah; Toh, Tsun-Haw; Goh, Khean-Jin; Loh, Ee-Chin; Capelle, David Paul; Abdul Latif, Lydia; Leow, Alex Hwong-Ruey; Yim, Carolyn Chue-Wai; Zainal Abidin, Mohd Fitry; Ruslan, Shairil Rahayu; Shahrizaila, Nortina
Abstract: Objective: Studies from multiethnic populations are rarely reported but do indicate differences in phenotypic presentation and survival in amyotrophic lateral sclerosis (ALS). In this study, we aimed to investigate the natural history of a cohort of ALS patients from a multiethnic population. Methods : Data from ALS patients presenting to our multidisciplinary ALS clinic were prospectively collected from January 2015 to June 2020 as part of an ongoing hospital-based patient registry. Kaplan–Meier and Cox regression model were performed to identify potential prognostic factors. Results : A total of 144 ALS patients were recruited. We estimated the crude ALS incidence as 0.53 per 100, 000 for 2019 but rises to 2 per 100, 000 in patients aged 60–74 years. The majority of patients were of Chinese ethnicity (59.7%), followed by Malay (24.3%), Indian (11.1%), and others (4.9%). Malaysian Indians had a significantly steeper ALSFRS-R slope at diagnosis ( p = 0.040). We found a worse prognosis in patients with bulbar-onset (HR = 1.915, p = 0.019), older age (HR = 1.052, p = 0.000), and who were fast-progressors (HR = 1.274, p = 0.000). In contrast, a higher body mass index (HR = 0.921, p = 0.007) and a longer time to diagnosis (HR = 0.967, p = 0.006), noninvasive ventilation (HR = 0.820, p = 0.000) and percutaneous endoscopic gastrostomy insertion (HR = 0.823, p = 0.000) were associated with better survival. On multivariate analysis, diagnostic delay and slow disease progression were associated with better survival. Conclusions : In our cohort, diagnostic delay and a slow disease progression were significantly associated with better survival in ALS. We also found ethnic variation with Chinese preponderance and more rapid disease progression in patients of Indian descent.